Wealth and poverty in early church and society - Holman, Susan R. 1956- (Grand Rapids, Mich. Baker Academic, 2008)
The New Testament period -- Injustice or God's will? : early Christian explanations of poverty / Steven J. Friesen -- "Be not one who stretches out hands to receive but shuts them when it comes to giving :" envisioning Christian charity when both donors and recipients are poor / Denise Kimber Buell -- James 2:2/7 in early Christian thought / George K. Hasselhoff -- Wealth, poverty, and the value of the person : some notes on the hymn of the pearl and its early Christian context / Edward Moore -- Egypt in late antiquity -- Widening the eye of the needle : wealth and poverty in the works of Clement of Alexandria / Annewies van den Hoek -- Care for the poor, fear of poverty, and love of money : Evagrius Ponticus on the monk's economic vulnerability / David Brakke -- Wine for widows : papyrological evidence for Christian charity in late antiquity Egypt / Adam Serfass -- Rich and poor in sophronius of Jerusalem's miracles of Saints Cyrus and John / Susan R. Holman -- John Chrysostom, the Cappadocians, and friends -- This sweetest passage : Matthew 25:31/46 and assistance to the poor in the homilies of John Chrysostom / Rudolf Brendle -- Poverty and generosity toward the poor in the time of John Chrysostom / Wendy Mayer -- Poverty and wealth as theater : John Chrysostom's homilies on Lazarus and the rich man / Francine Cardman -- Wealthy and impoverished widows in the writings of St. John Chrysostom / Efthalia Makris Walsh -- The hellenic background and nature of patristic philanthropy in the early Byzantine era / Demetrios J. Constantelos -- Wealth, trade, and profit in early Byzantium -- Gilding the lily : a patristic defense of liturgical splendor / A. Edward siecienski -- Wealth, stewardship, and charitable "blessings" in early Byzantine monasticism / Daniel Caner -- Trade, profit, and salvation in the late patristic and the Byzantine period / Angeliki E. Laiou -- Patristic studies for today -- St. Basil's philanthropic program and modern microlending -- Strategies for economic self-actualization / Timothy Patitsas -- The use of patristic socioethical texts in Catholic social thought / Brian Matz
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Wealth -- Congresses -- Religious aspects -- Christianity; Poverty -- Congresses -- Religious aspects -- Christianity; Church History -- Congresses -- Primitive and early church, ca. 30-600; Konferenzschrift -- 2005 -- Brookline, Mass